Determination of Tropomyosin in Shrimp and Crab by Liquid Chromatography–Tandem Mass Spectrometry Based on Immunoaffinity Purification - Fan, Sufang; Ma, Junmei; Li, Chunsheng; Wang, Yanbo; Zeng, Wen; Li, Qiang; Zhou, Jinru; Wang, Liming; Wang, Yi; Zhang, Yan (Frontiers in Nutrition, 2022)
An UPLC-MS/MS method was developed for the detection of tropomyosin (TM) in shrimp and crab. After simple extraction, the samples were purified by immunoaffinity column and then digested by trypsin. The obtained sample was separated by Easy-nLC 1000-Q Exactive. The obtained spectrums were analyzed by Thermo Proteome Discoverer 1.4 software, then ANIQLVEK with high sensitivity was selected as the quantitative signature peptide. The method showed a good linearity in the range of 5-5000 μg/L with the limit of quantification (LOQ) of 0.1 mg/kg. The average recoveries were 77.22% - 95.66% with RSDs ≤ 9.97%, and the matrix effects were between 88.53% - 112.60%. This method could be used for rapid screening and quantitative analysis of TM in shrimp and crab. Thus, it could provide technical support for self-testing of TM by food manufacturers, and promote the further improvement of allergen labeling in China.